What combinations of agomelatine with other antidepressants could be successful during the treatment of major depressive disorder or anxiety disorders in clinical practice?. (June 2019) - Potměšil, Petr
Even with many antidepressant and anxiolytic drugs available on the market, there are still patients who do not respond well to the standard first or second line treatments for affective or anxiety disorders. The antidepressant agomelatine has been used in Europe for several years. Agomelatine, an agonist at melatonin receptors and an antagonist at serotonin receptors, can be particularly useful in patients suffering from a major depressive disorder associated with insomnia. Some clinical data have shown a limited effect for agomelatine in a subset of patients with major depression. A number of case reports published in 2011-2016 describe the effect of agomelatine in combination with an established antidepressant, such as escitalopram, venlafaxine, duloxetine, moclobemide or bupropion. A successful combination of agomelatine was reported after adjunctive use of agomelatine combined with clomipramine, escitalopram, and venlafaxine in patients with major depression or obsessive–compulsive disorder. Moreover, bupropion or moclobemide augmentation with agomelatine in patients with major depressive disorder led to a significant improvement. Other supportive data have been published, such as analysis of the VIVALDI study, although it should be noted that the study was supported by the manufacturer of agomelatine. In this study, agomelatine in combination with other antidepressants was shown to be effective and well tolerated in practice, although the most effective antidepressant treatment in the study consisted of agomelatine alone and not in combination with other antidepressants. There have also been two published case reports about the concomitant use of duloxetine and agomelatine which were not efficacious. The positive results of agomelatine augmentation with other antidepressants should be confirmed through randomized, double-blind clinical trials.